Severe vaso-occlusive lupus retinopathy in the early stage of a pediatric patient with systemic lupus erythematosus: a case report. Issue 16 (April 2020) - Huang, Guoping; Shen, Huijun; Zhao, Jingli; Mao, Jianhua
Abstract: Introduction: Systemic lupus erythematosus (SLE) is a multisystem, chronic, autoimmune disease which can affect any organ system including the eye. About one-third of the patients can be diagnosed with SLE-related eye involvement which is usually indicative of disease activity. Retinopathy is one of the most vision-threatening complications that can be associated with the disease. Patient concerns: An 11-year-old girl was hospitalized with complains of repeated swelling and pain in her extremities for 1 month, chest pain for 24 days, rash for 5 days and proteinuria for 1 day. On the morning of her fourth day in hospital, she suddenly complained of sudden, painless vision loss in the left eye. The ophthalmologist found that she had obstruction of central retinal vein and artery with diffuse retinal hemorrhages and macular edema. Diagnosis: The patient was diagnosed with systemic lupus erythematosus, lupus nephritis, and lupus retinopathy through her clinical manifestations and laboratory tests. Interventions: After diagnosis, she received steroid therapy, retinal laser photocoagulation, and intravitreal injection of dexamethasone (OZURDEX, Allergan Pharmaceuticals, Dublin, Ireland) early in her course. Outcomes: At the latest follow-up, her vision improved partially. However, she still has the possibility of subsequent neovascular glaucoma and bleeding in the future. Conclusions: An early diagnosis and the prompt therapeutic measures are necessary to prevent sight-threatening consequences, especially in pediatric patients with SLE.